Virtual reality: Visualization for athletic competition - Levy, R.; Katz, L.; Sorrentino, R. M.; Peng, X. (International Journal of Computer Science in Sport, 2002)
This paper examines the user`s response to the representation of reality in a virtual world. Specifically, this research considers if visual environments can be created with sufficient realism to prepare an athlete for a first-time event in a foreign venue. Visualization techniques have been a critical component in training athletes for the psychological stress associated with a competition. Studies reveal that athletes` performance can benefit from programs that use some aspect of visualization (Hall, 1998; Martin, Moritz, & Hall, 1999). In events where the difference between the top placing athletes is less than one tenth of a second, preparation with visualization can be critical in winning an event. Evaluating the effectiveness and potential benefits of using different simulation environments in athletic training programs is a major focus of the Virtual Reality in Sport Research Group at the University of Calgary.